The The Effect of Black Soybean Flour Extract (Glycine soja) on Leukocyte Post Ovariectomy Implantation Mice (Mus musculus L.) - YENNY FEBRIANA RAMADHAN ABDI (Universitas Pasundan, 2018)
Black soybean is one type of plant that has estrogenic activity, it can act as a source of natural exogenous estrogen. Decreased estrogen hormone in the body can be caused due to ovariectomy and menopause, it can affect the activity and number of leukocytes in the reproduction of female. The purpose of this study was to determine the effect of black soybean flour extract to leukocytes post ovariectomy implant mice. This study used a completely randomized design (RAL) 4 treatments and each 7 replicated. Treatment 1 (negative control), treatment 2 (positive control: estradiol concentration 50 ppm), treatment 3 and 4 respectively with the administration of black soybean flour doses of 0.31 g / ml and 0.63 g / ml. The data were analyzed using One Way Anova test with a confidence level of 95% or α = 0.05 and further analyze with Duncan Multiple Range Test (DMRT). The results showed that the administration of black soybean flour extract for 10 days in post ovariectomy implantation mice showed a significant effect, doses of 0.31 g/ml and 0.63 g/ml increased the total number of leukocytes and the number of agranulocyte leukocytes.